Efectos de shocks de políticas fiscales en la economía ecuatoriana, período 1990-2007 - Gavilanes, Sara (2009)
This document researches the surprise effects that the Fiscal Policies generate in the Ecuadorian economy, specifically focused on establishing how fiscal expense shocks affect the inflation rates during the 1990-2007 period, for which Vector autoregressions were used (VAR). This analysis made it possible to conclude that with a positive government expense shock the general levels of prices in the Ecuadorian economy are pushed towards arise. However, there are further variables that have a greater incidence on the generation of inflation, such as the oil prices and rainfalls. The impulse-response function showed that an increment on the fiscal expenses with a standard deviation of 0.21% produces an increment on inflation of 0.003%. In other words, if the government expenses generate inflation, it was possible to prove that the exogenous variables have a greater incidence over the level of prices, for which, it is expected that the central government adopt policies to thwart the effects that these exogenous shocks generate and fulfill its stabilizing role, helping to smoothen the major fluctuations of national income and natural phenomena.